Can Stock Exchange inquiry letters reduce stock price crash risk?. Issue 8 (4th May 2021) - Li, Sihao; Shi, Yong; Zou, Wenjun
ABSTRACT: The inquiry letters of annual reports play an increasingly important role in performing the first-line supervision duties of Stock Exchange. Based on 2015–2017 annual report inquiry letters, this paper studies the impact of regulatory inquiry on stock price crash risk empirically. The results show that the Stock Exchange's inquiry on the annual report of listed companies reduces the stock price crash risk significantly, and the more questions are inquired by the Stock Exchange, the stronger inhibitory impact will be played on the companies' stock price crash risk . In addition, compared with companies replied to the inquiry letters in time, the inquiry has a stronger inhibitory effect on stock price crash risk of companies with delayed reply or no reply.